The Effect of trade sepecialization and institutional quality on Intra-Asean trade - A. Bakar, Norhayati (2017)
Intra-ASEAN trade is stagnant at 20% to 25% for the past few decades. This is partly because ASEAN members are overl-reliant on non-ASEAN countries for their exports. Several suggestions have been put forward such as exchange rates and trade agreement which observed so far as having limited effect to increase intra-ASEAN trade. In this study, we propose and examine the role of trade specialization and the quality of institutions among ASEAN for a period between 1996 and 2015. ASEAN countries are generally endowed with similar resources have a tendency to compete with each other for similar .products. Specialization in certain production, while leaving the other members to produce is theoretically helpful to promote trade among ASEAN.